2008
DOI: 10.1111/j.1365-2753.2008.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing experience: exploring the gap between evidence‐based medicine and clinical practice

Abstract: Clinical experience is relatively neglected by the EBM movement, but if that experience were systematically gathered through an approach such as EF, it would meet a need left unfulfilled by EBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 39 publications
(35 reference statements)
2
80
0
2
Order By: Relevance
“…Such an integrated investigator-practitioner role is recognized prominently in many disciplines such as education, agriculture, and engineering (Hay et al, 2008). The important distinction of a "top-down" model is that investigation addresses specific needs in an individual practice rather than producing universal knowledge or global evidence (Hay et al, 2008).…”
Section: The Basis Of the Conceptmentioning
confidence: 99%
See 4 more Smart Citations
“…Such an integrated investigator-practitioner role is recognized prominently in many disciplines such as education, agriculture, and engineering (Hay et al, 2008). The important distinction of a "top-down" model is that investigation addresses specific needs in an individual practice rather than producing universal knowledge or global evidence (Hay et al, 2008).…”
Section: The Basis Of the Conceptmentioning
confidence: 99%
“…The important distinction of a "top-down" model is that investigation addresses specific needs in an individual practice rather than producing universal knowledge or global evidence (Hay et al, 2008). Hay et al 2008 reported that improvements in patient care outcomes might be gained by balancing the global data of evidence-based medicine with locally relevant data through scientifically harnessing clinical experience.…”
Section: The Basis Of the Conceptmentioning
confidence: 99%
See 3 more Smart Citations